20 Characterizing durable targets for therapy in asymptomatic left ventricular diastolic dysfunction by sequential two-dimensional doppler-echocardiography and cardiac magnetic resonance imaging. (5th October 2017) - Voon, V; Waterhouse, D; Patle, A; Badabhagni, M; O'Hanlon, R; McDonald, K; Ledwidge, M
Abstract : Background: Two-dimensional Doppler-echocardiography (2 DE) remains the primary modality in assessing left ventricular diastolic dysfunction (LVDD) due to its widespread availability. In asymptomatic LVDD (ALVDD), the putative precursor of diastolic heart failure, 2 DE imaging of cardiac volume and mass has been reported to be prognostically significant. However, the consistency of such measures is not fully known with limited data on sequential imaging. We aimed to compare reproducibility of cardiac volumes and mass by sequential 2 DE against cardiac magnetic resonance imaging (CMR), the gold standard in evaluating volumes and mass, in patients with ALVDD. Methods: We sub-analysed imaging data from a prospective randomized clinical study (EudraCT 2010-021664-16) evaluating the impact of chronic doxycycline therapy on cardiac remodeling in patients with ALVDD, using 2 DE and CMR. Both modalities were performed by independent blinded observers at baseline, 6 months and 12 months. Cardiac volumes and mass were indexed to body surface area at each timepoint for all patients. Pearson's correlation was performed between measurements of both modalities at (baseline, 6 months, 12 months) respectively. Results were reported as mean ± SD. Results: All patients (n=48) had mean age 69.8 ± 8.5 years and ejection fraction (EF) 67 ± 7% at baseline. Sequential correlations in EF (0.20, 0.15, 0.34), p = 0.17, 0.32, 0.02 respectively; and left ventricular end-diastolic volume index (LVEDVi) (0.37, 0.17, 0.07), p = 0.01, 0.27, 0.65 respectively, were compared between both modalities. Modest but significant correlations were observed between 2 DE and CMR for left atrial volume index (LAVi) (0.39, 0.50, 0.45), left ventricular mass index (LVMi)(0.46, 0.30, 0.45) and left ventricular end-systolic volume index (LVESVi) ( 0.43, 0.58, 0.48 ); all p<0.05. Conclusion: 2 DE-measured EF and LVEDVi demonstrated a predominantly poor correlation with CMR. However, 2 DE demonstrated modest correlation in LAVI, LVMI and LVESVi. The reproducibility of these sequential measurements against CMR supports their use as durable targets for measuring impact of therapies for ALVDD.